Polyester resin, aqueous dispersion and adhesive composition using same
A polyester resin with 60 mol% diethylene glycol and a 20°C glass transition temperature, formulated into an aqueous dispersion, addresses adhesion issues to diverse packaging materials, enhancing adhesion and reducing solvent use.
Patent Information
- Application Number
- JP2021560046
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-06
- Filing Date
- 2021-03-26
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-03-26
AI Technical Summary
Existing polyester resins face challenges in achieving excellent adhesion to various packaging materials like polystyrene, polyvinyl chloride, and A-PET, often requiring additional polymer modification and using large amounts of organic solvents, which pose environmental issues.
A polyester resin with a specific composition containing 60 mol% diethylene glycol and a glass transition temperature of 20°C or less, formulated into an aqueous dispersion, which forms an adhesive layer of 1 to 10 μm thickness, enhancing adhesion to these materials.
The resin achieves excellent adhesion to polystyrene, polyvinyl chloride, and A-PET, suitable for food and pharmaceutical packaging, with improved water resistance and adhesiveness, reducing solvent use and environmental impact.
Smart Images

Figure 0007601001000001 
Figure 0007601001000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyester resin and a polyester resin aqueous dispersion, and also to an adhesive composition, a laminate and a packaging material each using the same. [Background technology]
[0002] Polyester resins are widely used as raw materials for resin compositions used in paints, coating agents, adhesives, etc. Polyester resins are generally composed of polycarboxylic acids and polyhydric alcohols. By selecting and combining the polycarboxylic acids and polyhydric alcohols, the molecular weight can be freely controlled, and the resulting polyester resins are used in a variety of applications, including paints and adhesives.
[0003] In the molecular design of polyester resins, the selection of copolymerization components is important. Polyvalent carboxylic acid components and polyhydric alcohol components can be broadly classified into aromatic, aliphatic, and alicyclic. The glass transition temperature, which indicates the flexibility of polyester resins, can be determined by the selection of these components. In terms of usage form, they are generally used by applying them to substrates as organic solvent-dissolved products or aqueous dispersions, but in recent years, aqueous dispersions have become particularly popular due to environmental concerns.
[0004] In recent years, materials in which a heat-sealable adhesive composition is applied to a substrate such as a polyester film or aluminum foil and then bonded together have been used as lid materials for various packaging containers made of polystyrene, polyvinyl chloride, A-PET (amorphous polyethylene terephthalate), polypropylene, etc. There is a demand for an aqueous heat-sealable adhesive composition that can be used for food applications and has excellent adhesion to all of these packaging containers.
[0005] For example, Patent Document 1 proposes an itaconic acid copolymerized polyester and a blend thereof, while Patent Document 2 proposes an aqueous dispersion containing a polyester resin (A) having a glass transition temperature of 50° C. or higher and a polyester resin (B) having a glass transition temperature of 30° C. or lower. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 5455377 [Patent Document 2] Patent No. 5241232 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0007] However, although Patent Document 1 shows good adhesion between aluminum foil coated with a heat-sealable adhesive composition and polystyrene or polypropylene, a process of further modifying the polymer is required to produce the resin, and the adhesive requires a large amount of organic solvent, which poses problems in terms of production and the environment. Furthermore, Patent Document 2 is an aqueous dispersion of polyester resin, but only evaluates the heat sealability between PET films, which are generally easy for polyester resin to adhere to, and there are concerns about adhesion to various substrates such as polystyrene, polyvinyl chloride, A-PET, and polypropylene.
[0008] As a result of extensive research aimed at solving the above problems, the present invention was completed after discovering a heat-sealable polyester resin that can be used for food and pharmaceutical applications and has excellent adhesion to various containers having different properties, such as polystyrene, polyvinyl chloride, and A-PET.
[0009] In other words, an object of the present invention is to provide a polyester resin and an aqueous dispersion thereof having excellent adhesion to various substrates such as polystyrene, polyvinyl chloride, and A-PET, as well as an adhesive composition, a laminate, and a packaging material each using the same. [Means for solving the problem]
[0010] As a result of extensive investigations, the present inventors have found that the above problems can be solved by the means described below, and have arrived at the present invention. That is, the present invention comprises the following configuration.
[0011] A polyester resin having a polycarboxylic acid component and a polyhydric alcohol component as structural units, in which when the polyhydric alcohol component is 100 mol %, the diethylene glycol component is 60 mol % or more, and the glass transition temperature is 20°C or less.
[0012] A polyester resin water dispersion containing the polyester resin.
[0013] An adhesive composition comprising the above-mentioned polyester resin aqueous dispersion.
[0014] A laminate comprising an adhesive layer made of the adhesive composition and a thermoplastic resin film or an aluminum foil.
[0015] The thickness of the adhesive layer is preferably in the range of 1 to 10 μm.
[0016] The laminate can be preferably used as a packaging material.
[0017] The packaging material can be preferably used as a blister pack, a lid material and a food packaging container. Effect of the Invention
[0018] The polyester resin and aqueous dispersion of the present invention have excellent adhesion to various substrates such as polystyrene, polyvinyl chloride, A-PET, etc. Therefore, a heat-sealable adhesive composition can be easily formed, and it can be suitably used as a packaging material for food packaging, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, an embodiment of the present invention will be described in detail.
[0020] <Polyester resin> The polyester resin of the present invention has a chemical structure that can be obtained by polycondensation of a polycarboxylic acid component and a polyhydric alcohol component, and the polycarboxylic acid component and the polyhydric alcohol component each consist of one or more selected components.
[0021] The polyvalent carboxylic acid component constituting the polyester resin of the present invention is preferably an aromatic dicarboxylic acid, an alicyclic dicarboxylic acid and / or an aliphatic dicarboxylic acid.
[0022] When the total amount of the polyvalent carboxylic acid components is taken as 100 mol%, the copolymerization amount of the aromatic dicarboxylic acid is preferably 55 mol% or more, more preferably 60 mol% or more, and even more preferably 65 mol% or more. If the copolymerization amount of the aromatic dicarboxylic acid is less than 55 mol%, the water resistance may decrease.
[0023] When the total amount of polyvalent carboxylic acid components is 100 mol%, the copolymerization amount of alicyclic dicarboxylic acid and / or aliphatic dicarboxylic acid is preferably 50 mol% or less, more preferably 40 mol% or less, and even more preferably 30 mol% or less. By making it 50 mol% or less, the hydrolysis resistance of the polyester resin is improved and the water resistance is good. When alicyclic and / or aliphatic dicarboxylic acid are copolymerized, it is preferably 5 mol% or more, more preferably 10 mol% or more. By making it 5 mol% or more, the adhesiveness is improved.
[0024] As a specific example of a suitable polyvalent carboxylic acid component, it is preferable to use terephthalic acid, 1,4-cyclohexanedicarboxylic acid, isophthalic acid, orthophthalic acid, 2,6-naphthalenedicarboxylic acid, dimethyl 2,6-naphthalenedicarboxylate, trimellitic acid, adipic acid, sebacic acid, fumaric acid, maleic acid or dimer acid, which may be used alone or in combination of two or more. These compounds are raw materials described and approved in FDA (Food and Drug Administration) standard 175.300 (b) (3) (vii) (revised version April 1, 2019), and can be suitably used for food packaging materials. Among these, it is preferable to combine terephthalic acid, isophthalic acid, orthophthalic acid, 1,4-cyclohexanedicarboxylic acid, or sebacic acid in terms of adhesion to substrates, water resistance, price, etc.
[0025] When the total amount of the polyhydric alcohol components is 100 mol%, the copolymerization amount of diethylene glycol must be 60 mol% or more, preferably 65 mol% or more, more preferably 70 mol% or more, and may be 100 mol%. By making it 60 mol% or more, the adhesion to various containers such as polystyrene, polyvinyl chloride, and A-PET is improved. Diethylene glycol is a compound listed in FDA standard 175.300(b)(3)(vii) (revised version of April 1, 2019).
[0026] As the polyhydric alcohol component other than diethylene glycol, it is preferable to use a compound described in FDA Standard 175.300(b)(3)(vii) (revised version on April 1, 2019). Specific examples of these include ethylene glycol, 1,4-butanediol, triethylene glycol, propylene glycol, 2,2-dimethyl-1,3-propanediol, glycerol, mannitol, pentaerythritol, trimethylolethane, and trimethylolpropane. The copolymerization amount of these polyhydric alcohol components must be 40 mol% or less, preferably 35 mol% or less, more preferably 30 mol% or less, and may be 0 mol%, assuming that the total amount of the polyhydric alcohol components is 100 mol%. These polyhydric alcohols may be used alone or in combination of two or more types.
[0027] In the polyester resin of the present invention, it is also preferable to introduce a branched structure by copolymerizing a small amount of a trifunctional or higher polyvalent carboxylic acid component or a polyhydric alcohol component. This makes it possible to form a tougher layer of the adhesive composition (hereinafter also referred to as an adhesive layer), and the effect of improving water resistance and adhesion can be exhibited. Specific examples include trimellitic anhydride, ethylene glycol bisanhydrotrimellitate, trimethylolpropane, glycerin, and pentaerythritol. The copolymerization amount of these trifunctional or higher polyvalent carboxylic acid components and polyhydric alcohol components is preferably 0.5 mol% or more, more preferably 1 mol% or more, when the total amount of all polyvalent carboxylic acid components and all polyhydric alcohol components is 200 mol%. In addition, it is preferably 5 mol% or less, more preferably 4 mol% or less, and even more preferably 3 mol% or less.
[0028] When the total amount of the polyvalent carboxylic acid components is taken as 100 mol%, the content of the aromatic dicarboxylic acid component having a sulfonate group is preferably less than 1 mol%. More preferably, it is 0.5 mol% or less, even more preferably, it is 0.1 mol% or less, and particularly preferably, it is 0 mol%. Since the aromatic dicarboxylic acid component having a sulfonate group is an acid component not approved by the FDA, the polyester resin of the present invention can be used for food contact applications by reducing the amount of the aromatic dicarboxylic acid component having a sulfonate group. Examples of the aromatic dicarboxylic acid component having a sulfonate group include 5-sulfoisophthalic acid, 4-sulfonaphthalene-2,7-dicarboxylic acid, 5[4-sulfophenoxy]isophthalic acid, and alkali metal salts thereof. Examples of the alkali metal salt include lithium, sodium, potassium, and the like. Specific examples include sodium 5-sulfonatoisophthalate, potassium 5-sulfonatoisophthalate, sodium 4-sulfonaphthalene-2,7-dicarboxylate, sodium 5[4-sulfophenoxy]isophthalate, and the like.
[0029] When the total amount of the polyhydric alcohol components is taken as 100 mol%, the content of the polyhydric alcohol component having a sulfonate group is preferably less than 1 mol%. More preferably, it is 0.5 mol% or less, even more preferably, it is 0.1 mol% or less, and particularly preferably, it is 0 mol%. Since the polyhydric alcohol component having a sulfonate group is an alcohol component not approved by the FDA, the polyester resin of the present invention can be used for food contact applications by reducing the amount of the polyhydric alcohol component having a sulfonate group. Examples of the polyhydric alcohol component having a sulfonate group include the sodium salt of 2-sulfo-1,4-butanediol and the sodium salt of 2,5-dimethyl-3-sulfo-2,5-hexanediol.
[0030] In addition, in order to impart an acid value, an acid anhydride such as trimellitic anhydride or pyromellitic anhydride may be added after polymerization of the polyester resin. Specific examples of the acid anhydride for imparting an acid value include trimellitic anhydride, pyromellitic anhydride, and ethylene glycol bisanhydrotrimellitate, and one or more of these may be used. When added after the fact, the total amount of the polyvalent carboxylic acid component and the polyhydric alcohol component may exceed 200 mol%. In this case, the total amount of the composition excluding the component to which the acid anhydride is added after the fact is calculated as 200 mol%.
[0031] When producing the polyester resin of the present invention, the polymerization catalyst that can be used includes, for example, titanium compounds such as tetra-n-butyl titanate, tetraisopropyl titanate, and titanium oxyacetylcetonate, antimony compounds such as antimony trioxide and tributoxyantimony, germanium compounds such as germanium oxide and tetra-n-butoxygermanium, and acetates of magnesium, iron, zinc, manganese, cobalt, and aluminum. These catalysts can be used alone or in combination of two or more.
[0032] The method of the polymerization condensation reaction for producing the polyester resin of the present invention is not particularly limited, and examples thereof include 1) a method of heating a polycarboxylic acid and a polyhydric alcohol in the presence of an arbitrary catalyst, passing through a dehydration esterification step, and then carrying out a polyhydric alcohol removal / polycondensation reaction, and 2) a method of heating an alcohol ester of a polycarboxylic acid and a polyhydric alcohol in the presence of an arbitrary catalyst, passing through an ester exchange reaction, and then carrying out a polyhydric alcohol removal / polycondensation reaction, etc. In the above methods 1) and 2), a part or all of the acid component may be replaced with an acid anhydride.
[0033] The glass transition temperature (Tg) of the polyester resin of the present invention is 20° C. or lower. It is preferably −5 to 20° C., more preferably 0 to 20° C., and even more preferably 5 to 15° C. By making it equal to or higher than the lower limit, it is possible to suppress the occurrence of blocking when the laminated film is wound into a roll. By making it equal to or lower than the upper limit, the resin has flexibility even when peeled off at room temperature, and the adhesiveness is good.
[0034] The reduced viscosity (ηsp / c) of the polyester resin of the present invention is preferably 0.2 to 0.9 dl / g. More preferably, it is 0.3 to 0.8 dl / g, and further preferably, it is 0.4 to 0.7 dl / g. By making it equal to or more than the lower limit, the resin coagulation force becomes good, and excellent adhesiveness can be exhibited. Also, by making it equal to or less than the upper limit, an aqueous dispersion can be prepared. The reduced viscosity can be arbitrarily adjusted by changing the polymerization time, temperature, and degree of reduced pressure during polymerization (in the case of reduced pressure polymerization) of the polyester resin.
[0035] The acid value of the polyester resin of the present invention is preferably 50 to 600 eq / t. More preferably, it is 100 to 550 eq / t, and even more preferably, it is 150 to 500 eq / t. By making it equal to or less than the upper limit, the molecular weight is not low, so that the resin cohesive force is good and excellent adhesiveness can be exhibited. In addition, by making it equal to or more than the lower limit, the aqueous dispersion can be easily prepared.
[0036] The number average molecular weight (Mn) of the polyester resin of the present invention is preferably 4000 to 40000. More preferably, it is 6000 to 35000, and further preferably, it is 8000 to 30000. By making it equal to or more than the lower limit, the resin coagulation force becomes good, and excellent adhesiveness can be exhibited. Also, by making it equal to or less than the upper limit, an aqueous dispersion can be prepared. The number average molecular weight can be arbitrarily adjusted by changing the polymerization time, temperature, and degree of reduced pressure during polymerization (in the case of reduced pressure polymerization) of the polyester resin. The number average molecular weight is a value measured by gel permeation chromatography (hereinafter, GPC, standard substance: polystyrene resin, mobile phase: tetrahydrofuran or chloroform).
[0037] <Polyester resin water dispersion> The polyester resin aqueous dispersion of the present invention is an aqueous dispersion containing the above-mentioned polyester resin and water, and optionally containing an organic solvent.
[0038] The boiling point of the organic solvent used in the polyester resin water dispersion of the present invention is preferably 60°C or higher, more preferably 70°C or higher, and even more preferably 80°C or higher. When the boiling point is 60°C or higher, the solvent is easy to handle during coating from the viewpoint of volatility. In addition, the boiling point is preferably 180°C or lower, more preferably 175°C or lower, even more preferably 170°C or lower, particularly preferably 165°C or lower, and most preferably 160°C or lower. When the boiling point is 180°C or lower, there is almost no residual solvent during drying, and problems such as blocking during winding do not occur.
[0039] The organic solvent used in the polyester resin water dispersion of the present invention is not particularly limited, but includes alcohols such as isopropyl alcohol, isobutyl alcohol, and isoamino alcohol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether (hereinafter also referred to as "n-butyl cellosolve" or "n-BuCS"), ethylene glycol mono-tert-butyl ether (hereinafter also referred to as "t-butyl cellosolve" or "t-BuCS"), propylene glycol monobutyl ether, and methyl ethyl ketone. These organic solvents can be used alone or in combination of two or more. Among them, isopropyl alcohol, n-butyl cellosolve, and t-butyl cellosolve are particularly preferred.
[0040] The organic solvent is preferably 200 parts by mass or less, more preferably 150 parts by mass or less, and even more preferably 100 parts by mass or less, relative to 100 parts by mass of the polyester resin. By making it less than the upper limit, the residual solvent during drying is reduced, and problems such as blocking during winding are prevented. In addition, the storage stability is also good. The lower limit is not particularly limited, and the solvent may be completely removed by vacuum concentration after dispersing the resin, but industrially, it is no problem if it is contained in an amount of 1 part by mass or more, and it is also acceptable if it is contained in an amount of 10 parts by mass or more.
[0041] The particle size of the polyester resin phase contained in the polyester resin aqueous dispersion of the present invention is preferably 30 nm or more, more preferably 40 nm or more, even more preferably 50 nm or more, and particularly preferably 60 nm or more. By making it equal to or more than the lower limit, the film-forming property is improved, fusion and aggregation between dispersed particles are suppressed, and thickening and poor dispersion do not occur. In addition, it is preferably 500 nm or less, more preferably 450 nm or less, and even more preferably 400 nm or less. By making it equal to or less than the upper limit, excellent dispersion stability and film-forming property can be maintained, and the appearance and performance of the obtained film become good. Here, the particle size refers to the particle size of the polyester resin, and when two or more polyester resins are contained, such as further containing another polyester resin, it refers to the average particle size of two or more polyester resins.
[0042] The polyester resin water dispersion of the present invention can be suitably used as a raw material for adhesives, coating agents and heat sealing agents, and is particularly suitable for adhesive applications.
[0043] <Adhesive composition> The adhesive composition of the present invention is a composition containing the above-mentioned polyester resin aqueous dispersion as an essential component.
[0044] The adhesive composition of the present invention may be blended with other polyester resins or aqueous dispersions thereof, and various additives, as long as the performance of the present invention is not impaired. The additives are not particularly limited, but it is preferable to use an antiblocking agent or the like.
[0045] Examples of the antiblocking agent include inorganic particles, organic particles, waxes, etc., and can be contained to the extent that the adhesiveness and antiblocking properties are not deteriorated. These antiblocking agents can be used alone or in combination of two or more. When an antiblocking agent is contained, it is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, relative to 100 parts by mass of the polyester resin. By containing the antiblocking agent in an amount equal to or more than the lower limit, the antiblocking effect can be expressed. In addition, it is preferably 20 parts by mass or less, more preferably 15 parts by mass or less. By containing the antiblocking agent in an amount equal to or less than the upper limit, the adhesiveness can be maintained.
[0046] Examples of inorganic particles include inorganic particles containing oxides, hydroxides, sulfates, carbonates, or silicates of metals such as magnesium, calcium, barium, zinc, zirconium, molybdenum, silicon, antimony, or titanium. Among these inorganic particles, silica gel particles are particularly preferred. The shape of the particles is not limited and may be any shape such as powder, granules, granules, platelets, or needles.
[0047] Examples of organic particles include polymer particles such as polymethyl methacrylate resin, polystyrene resin, nylon resin, melamine resin, benzoguanamine resin, phenol resin, urea resin, silicone resin, methacrylate resin, or acrylate resin, or cellulose powder, nitrocellulose powder, wood powder, waste paper powder, rice husk powder, starch, etc. The polymer particles can be obtained by polymerization methods such as emulsion polymerization, suspension polymerization, dispersion polymerization, soap-free polymerization, and microsuspension polymerization. The organic particles can be used within a range that does not impair the effects of the present invention. The shape of the particles is not limited and may be any shape such as powder, granule, granular, plate-like, or needle-like.
[0048] Specific examples of waxes include liquid paraffin, natural paraffin, microwax, synthetic paraffin, hydrocarbon waxes such as polyethylene wax, fatty acid waxes such as stearic acid, fatty acid amide waxes such as stearic acid amide, palmitic acid amide, methylene bis stearamide, ethylene bis stearamide, oleic acid amide, and esylic acid amide, ester waxes such as lower alcohol esters of fatty acids, polyhydric alcohol esters of fatty acids, and fatty acid polyglycol esters, alcohol waxes such as cetyl alcohol and stearyl alcohol, olefin waxes, natural waxes such as castor wax and carnauba wax, and metal soaps derived from fatty acids having 12 to 30 carbon atoms. The waxes can be used within a range that does not impair the effects of the present invention.
[0049] <Laminate> The laminate of the present invention is a film or metal foil having an adhesive layer made of the adhesive composition of the present invention laminated on at least one side of a film or metal foil serving as a substrate, which is obtained by applying the adhesive composition to the film or metal foil serving as a substrate and then carrying out a drying treatment.
[0050] The film to be the substrate is not particularly limited as long as it can form an adhesive layer from the adhesive composition of the present invention, but is preferably a thermoplastic resin film or a metal-coated thermoplastic film. For example, examples of the thermoplastic resin film include polyester-based resin film, polypropylene-based resin film, polyamide-based resin film, polyvinyl alcohol-based resin film, and polyvinylidene chloride-based resin film. Among them, polyester-based resin film is more preferable because it is suitable as a lid material for food packaging containers. In addition, examples of the metal-coated film include aluminum-deposited film and inorganic filler-deposited film such as alumina and / or silicon.
[0051] The metal foil used as the substrate is not particularly limited as long as it is capable of forming an adhesive layer from the adhesive composition of the present invention. However, aluminum foil is preferred because it is suitable for use as a lid material for food packaging containers and blister packs for pharmaceuticals.
[0052] The laminate of the present invention has excellent adhesiveness, and is therefore suitable as a component of packaging materials and blister packs for pharmaceuticals and the like. In particular, it is suitable as a lid material for food packaging containers for processed foods such as fresh food and yogurt. When used as a lid material for food packaging containers, the adhesive layer surface of the laminate and the food packaging container can be heat-sealed to seal the contents. The food packaging container is not particularly limited, but is preferably a polyester-based resin, a polystyrene-based resin, a polyvinyl chloride-based resin, or a polypropylene-based resin. EXAMPLES
[0053] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the examples. In the examples and comparative examples, parts simply indicate parts by mass.
[0054] (Physical property evaluation method)
[0055] Determination of polyester resin composition 400MHz 1 H-nuclear magnetic resonance spectrometer ( 1 The molar ratios of the polyvalent carboxylic acid and polyhydric alcohol components constituting the polyester resin were determined using H-NMR. Deuterated chloroform was used as the solvent.
[0056] Glass transition temperature (Tg) Using a differential scanning calorimeter (DSC) DSC-220 manufactured by Seiko Instruments Inc., 5 mg of a sample (heat-sealable polyester resin) was sealed in an aluminum press-lid type container and measured from -100°C to 250°C at a heating rate of 20°C / min. The temperature was determined as the temperature at the intersection of an extension of the baseline below the glass transition temperature and a tangent showing the maximum slope between the rising part of the peak and the top of the peak.
[0057] Measurement of reduced viscosity (unit: dl / g) The measurements were performed using an Ubbelohde viscosity tube with a polyester resin sample concentration of 0.1 g / 25 ml, measurement solvent phenol / tetrachloroethane (mass ratio 6 / 4), and measurement temperature of 30°C.
[0058] Acid Number Measurement 0.2 g of a polyester resin sample was dissolved in 40 ml of chloroform and titrated with 0.01 N potassium hydroxide ethanol solution to obtain 10% polyester resin. 6 The equivalent weight per gram (eq / t) was calculated. Phenolphthalein was used as the indicator.
[0059] Storage stability The polyester resin aqueous dispersion was stored (left stationary) at 25°C for 6 months, and the changes in appearance and shape (viscosity) were observed. <Evaluation criteria> ○: No change in appearance or shape (viscosity). △: Became cloudy but the shape (viscosity) did not change. ×: Viscosity increased, separation occurred, or poor dispersion occurred.
[0060] Preparation of laminated film and laminated aluminum foil for evaluation The adhesive compositions obtained in the Examples and Comparative Examples were applied to aluminum foil having a thickness of about 20 μm so that the thickness after drying would be 4 to 5 μm, and then dried at 150° C. for 30 seconds to obtain laminated aluminum foil for evaluation.
[0061] Peel strength (adhesion) The adhesive layer of the laminated aluminum foil for evaluation was placed against the substrates of A-PET sheet, polystyrene sheet, and polyvinyl chloride sheet, each of which had a thickness of approximately 850 μm, at a temperature of 200°C and a pressure of 4.5 kgf / cm. 2 Then, a test piece having a width of 15 mm was cut out and subjected to a 180° peel test at a tensile speed of 100 mm / min at 25° C. to measure the peel strength. <Evaluation criteria> ◎: 1000gf / 15mm or more for all substrates ○: 800gf / 15mm or more for all substrates ×: Some substrates do not reach 800gf / 15mm
[0062] Synthesis of polyester resin (A-1) In a reaction vessel equipped with a stirrer, a thermometer, a heater, a cooling device, and a distillation cooler, 534 parts by mass of isophthalic acid, 141 parts by mass of 1,4-cyclohexanedicarboxylic acid, 12 parts by mass of trimellitic anhydride, 652 parts by mass of diethylene glycol, and 0.5 parts by mass of tetrabutyl titanate were charged, and the temperature was raised to 220 ° C. while carrying out an esterification reaction for 4 hours. After the esterification reaction was completed, the pressure in the system was raised to 250 ° C. while reducing the pressure to 10 torr over 60 minutes, and the pressure was further reduced to a vacuum of 1 torr or less, and a polycondensation reaction was carried out at 250 ° C. until a predetermined viscosity was reached. Thereafter, nitrogen was flowed into the system, the system was cooled to 220 ° C., and 24 parts by mass of trimellitic anhydride was added, and the reaction was carried out for 30 minutes. After the reaction was completed, the polyester resin was taken out and cooled to obtain polyester resin (A-1). The resin composition and the measurement results of physical properties are shown in Table 1.
[0063] Synthesis of polyester resins (A-2) to (A-12) Similarly to the synthesis example of polyester resin (A-1), polyester resins (A-2) to (A-12) were synthesized by changing the types and blending ratios of raw materials. The resin compositions and the measurement results of physical properties are shown in Table 1.
[0064] [Table 1]
[0065] Example 1 Production Example of Polyester Resin Water Dispersion (B) Production of polyester resin aqueous dispersion (B-1) The polyester resin (A-1) was dispersed in water according to the following procedure. 990 parts of polyester resin (A-1), 578 parts of isopropanol, 1733 parts of water, and 18 parts of 28% aqueous ammonia were charged into a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and stirred at 75°C for 4 hours. After cooling to room temperature, the mixture was removed from the reaction vessel to obtain a polyester resin water dispersion (B-1). The results of various property evaluations are shown in Table 2.
[0066] Examples 2 to 8, Comparative Examples 1 to 4 Polyester resin water dispersions (B-2) to (B-12) were obtained by changing the type of polyester resin in the same manner as in the production example of Example 1. The results of evaluation of various characteristics are shown in Table 2.
[0067] [Table 2]
[0068] As is clear from Table 2, Examples 1 to 8 show good adhesion to three types of substrates. On the other hand, Comparative Examples 1 to 3 show low adhesion to some substrates due to the small amount of diethylene glycol. Comparative Example 4 shows low adhesion despite the large amount of diethylene glycol due to its high Tg. [Industrial Applicability]
[0069] The adhesive composition containing the polyester resin according to the present invention and the laminate using the same have excellent adhesion to various types of substrates when heat-sealed as a lid material for a packaging container.
Claims
1. A packaging material having as a component a laminate formed by laminating an adhesive layer and a thermoplastic resin film or an aluminum foil, the adhesive layer is made of an adhesive composition containing a polyester resin aqueous dispersion containing a polyester resin, the polyester resin has a polycarboxylic acid component and a polyhydric alcohol component as structural units, and the diethylene glycol component is 60 mol % or more when the polyhydric alcohol component is 100 mol %, the content of the aromatic dicarboxylic acid component having a sulfonate group is 0.1 mol % or less when the total amount of the polyvalent carboxylic acid components is taken as 100 mol %, The acid value of the polyester resin is 150 to 500 eq / t, A packaging material in which the glass transition temperature of the polyester resin is -5°C or higher and 20°C or lower, the glass transition temperature being determined by using a differential scanning calorimeter to seal 5 mg of the polyester resin in an aluminum lidded container and measure the temperature from -100°C to 250°C at a temperature increase rate of 20°C / min, as measured as the temperature at the intersection of an extension of a baseline below the glass transition temperature and a tangent showing the maximum slope between the rising part of the peak and the apex of the peak.
2. 2. The packaging material according to claim 1, wherein the thickness of the adhesive layer is in the range of 1 to 10 μm.
3. A blister pack having the packaging material according to claim 1 or 2 as a component thereof.
4. A lid material for food packaging containers, comprising the packaging material according to claim 1 or 2 as a constituent element.
5. A food packaging container comprising a laminate of the covering material according to claim 4 and a polyester resin or an aluminum foil.
Citation Information
Patent Citations
Weed killer
JP1977041232A
Water soluble or water dispersibility branched copolyester and preparation thereof
JP1978007797A
End point detection method in dry etching
JP1979055377A
Production of aqueous polyester dispersion and its use
JP1989284548A
Water-dispersible adhesive composition and method
JP1997507875A
